2020
DOI: 10.3390/pathogens9030218
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent Mechanisms of Macrophage Apoptosis Subversion by Mycobacterium

Abstract: Macrophages are one of the first innate defense barriers and play an indispensable role in communication between innate and adaptive immune responses, leading to restricted Mycobacterium tuberculosis (Mtb) infection. The macrophages can undergo programmed cell death (apoptosis), which is a crucial step to limit the intracellular growth of bacilli by liberating them into extracellular milieu in the form of apoptotic bodies. These bodies can be taken up by the macrophages for the further degradation of bacilli o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…Moreover, Mtb has evolved a series of intelligent strategies to hijack host cell miRNAs to subvert the abovementioned functions and achieve immune evasion [ 3 ]. Numerous emerging studies have revealed that miRNAs can manipulate host macrophage defence against Mtb infection [ 4 , 5 ], but a detailed and comprehensive understanding of the mechanisms remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Mtb has evolved a series of intelligent strategies to hijack host cell miRNAs to subvert the abovementioned functions and achieve immune evasion [ 3 ]. Numerous emerging studies have revealed that miRNAs can manipulate host macrophage defence against Mtb infection [ 4 , 5 ], but a detailed and comprehensive understanding of the mechanisms remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Apoptosis, or programmed cell death, is an important host defense mechanism against infection as it can promote pathogen clearance and resolution of inflammation [ 73 ]. M.tb has evolved various strategies for inhibition of apoptosis, ranging from the inhibition of calcium influx, suppressing cell death pathways, or promoting the expression of anti-apoptotic factors [ 74 , 75 ]. Our lab recently identified one such mechanism, in which M.tb induces the expression of the peroxisome proliferator-activated receptor (PPAR)γ in human MDMs, which in turn drives the expression of Mcl-1, a pro-survival member of the Bcl-2 family.…”
Section: Cellular Pathwaysmentioning
confidence: 99%
“…Concerning the macrophages reprogramming capability, Abdalla A.E. and co-authors contribute to the Special Issue with a review discussing the multiple mechanisms adopted by MTB to interfere with macrophage apoptosis [26]. In particular, they describe the anti-apoptotic determinants, listing the mechanism of action and the main molecular outcome.…”
Section: Editorialmentioning
confidence: 99%